Comparison of the Safety and Efficacy of Interferon Alpha-2a and Cyclosporine-A When Combined With Glucocorticoid in the Treatment of Refractory Behçet’s Uveitis: A Randomized Controlled Prospective Study - Qian, Yujing; Qu, Yi; Gao, Fei; Pei, Minghang; Liang, Anyi; Xiao, Junyan; Zhao, Chan; Zhang, Meifen (Frontiers in Pharmacology, 2021)
Purpose: To evaluate and compare the efficacy and safety of interferon alpha-2a (IFN-α2a) and cyclosporine-A (CsA) in patients with refractory Behçet’s uveitis (BU). Methods: In this 12-month randomized, controlled, prospective trial, 26 participants (44 eyes) completed the study. Patients were randomly allocated to the IFN-α2a or CsA groups. All patients in both groups received a standardized prednisone burst and tapering schedule as per protocol. The primary outcome measures were response rate, complete remission rate, and tolerance rate. The secondary outcome measures included time to achieve complete remission, the logarithm of the minimum angle of resolution (logMAR) of best-corrected visual acuity (BCVA), and Behçet's disease ocular attack score 24 (BOS24). T-tests and non-parametric tests were used to compare quantitative variables, and chi-square tests were performed to compare qualitative variables. Results: The response and complete remission rates were 85.7% (12/14 patients) and 50.0% (7/14 patients) in the IFN-α2a group, compared with 66.7% (8/12 patients) and 25.0% (3/12 patients) in the CsA group, respectively (p>0.05). Complete remission was achieved at 3.3 and 7.0 months after initiation of IFN-α2a and CsA (p=0.023). LogMAR BCVA significantly improved 1 month after IFN-α2a initiation (23 eyes) (p=0.002), and this beneficial effect remained statistically significant during the entire follow-up period (p<0.05); however, this improvement was not observed in the CsA group (21 eyes). At the endpoint, LogMAR BCVA in the IFN-α2a group was significantly better (0.22 vs 0.31, p=0.031) with a higher improvement rate (60.9% vs. 47.6%, p>0.05). Moreover, compared to the CsA group, more eyes in the IFN-α2a group had a lower BOS24 score (87.0% vs. 57.1%, p=0.042). None of the patients had any side effects that influenced the medication adherence. Conclusions: Compared to CsA plus corticosteroid, IFN-α2a plus corticosteroid appears to induce a better treatment response, a significantly greater improvement in visual acuity, and more stable remission of intraocular inflammation in a 12-month study period.